Performance of Asorwa Waste Stabilization Ponds and the Condition of Other Sewage Treatment Plants in Ghana (Journal of Science and Technology, 2016)
The performance of a functional waste stabilization pond among a series of three neglected ones, was evaluated during a two-month period for its operational efficiency. The relevant parameters measured were flow rates, pH, dissolved oxygen, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total solids, total bacterial, conform counts, nitrate nitrogen, ammonia nitrogen and phosphorus in samples of both the influent and effluent. The influent flaw rate of 290 m3 per day was higher than the design value of 270 m.1 per day. The effluent flow rate was 230 in-1 per day. The detention period of 8.31 days was markedly different from the design value of 53.76 days. The pond's efficiency as deter, mined by the measurements of BOD, COD, sus-pended solids and total bacteria plate count, indicated that the pond can still handle more wastes without failing. Its organic (i.e., HOD) loading was 256 kg ha/day compared to maxi-mum capacity of 635 kg ha/day obtained Lty using the empirical formula (11.2) (1.054)1. The pond was, however, inefficient in the removal of ammonia nitrogen and conforms. The condition of other Sewage Treatment Plants inspected between 1988-1991 showed that most of these plants have been neglected and need rehabilitation and properly trained personnel to operate and maintain them.